If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -3w = 7w + 64 Reorder the terms: 24 + -3w = 64 + 7w Solving 24 + -3w = 64 + 7w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-7w' to each side of the equation. 24 + -3w + -7w = 64 + 7w + -7w Combine like terms: -3w + -7w = -10w 24 + -10w = 64 + 7w + -7w Combine like terms: 7w + -7w = 0 24 + -10w = 64 + 0 24 + -10w = 64 Add '-24' to each side of the equation. 24 + -24 + -10w = 64 + -24 Combine like terms: 24 + -24 = 0 0 + -10w = 64 + -24 -10w = 64 + -24 Combine like terms: 64 + -24 = 40 -10w = 40 Divide each side by '-10'. w = -4 Simplifying w = -4
| 2(-2b+5)-5b=-20+6b | | -(-2w-31)=30 | | -9(4x-2)=108-16 | | (a^3-2a^2)-(3a^2-4a^2)= | | 100000=x-.08x-260000 | | (X-2)-2(x-1)=(x+1)-(x-6) | | 46=47+1x | | cos(3x)=10x^2 | | 1260/m=20 | | 1260/m=20 | | 7x+5=8-x | | 2x+0.2=x-3 | | 80h-2=15 | | 2(x-6)=7x | | 80h-2= | | 12=z-5/3 | | 10a-3a=8+8a | | 2x+1=81 | | 12=z-5/4 | | 36x^2+24x-13=0 | | 22=6x^2+5x+1 | | 80-2=15f | | -4x-13=27 | | p^2z^3+p^3z^4-p^4z^5=0 | | w/(w-3)-2w/(2x-1)=(w-3)/(2w^2-7w+3) | | 10+R=4R | | -31=8-p | | 80-2d=15 | | 9(z+6)=8(z-4)+2 | | 4/5x3/11x1/4 | | 4a/9-5a/6 | | (7x+2)(7x+2)=36 |